PLS BARDZO SZYBKO
Metodą podstawiania
![PLS BARDZO SZYBKO Metodą Podstawiania class=](https://pl-static.z-dn.net/files/dc7/773c96fcbdff27bbd9f19fc61e92c81e.jpg)
Odpowiedź:
Szczegółowe wyjaśnienie:
Rozwiązanie w załączniku.
Skorzystałem ze wzorów skróconego mnożenia:
[tex](a-b)^2=a^2-2ab+b^2\\\\(a+b)^2=a^2+2ab+b^2\\\\(a-b)(a+b)=a^2-b^2[/tex]
Odpowiedź:
[tex]\begin{cases}(x-2)^2-y(y+2)=-y^2+(x-3)^2+5\\x(x+6)-(y+1)^2=-(y+2)(y-2)-19+x^2\end{cases}\\\\\\\begin{cases}x^2+4x-4-y^2-2y=-y^2+x^2-6x+9+5\\x^2+6x-(y^2+2y+1)=-(y^2-4)-19+x^2\end{cases}\\\\\\\begin{cases}x^2-4x-y^2-2y+y^2-x^2+6x=14-4\\x^2+6x-y^2-2y-1=-y^2+4-19+x^2\end{cases}\\\\\\\begin{cases}2x-2y=10\\x^2+6x-y^2-2y+y^2-x^2=-15+1\end{cases}\\\\\\\begin{cases}2x-2y=10\\6x-2y=-14\ \ /\cdot(-1)\end{cases}[/tex]
[tex]+\begin{cases}2x-2y=10\\-6x+2y=14\end{cases}\\---------\\-4x=24\ \ /:(-4)\\x=-6\\\\\\2\cdot(-6)-2y=10\\\\-12-2y=10\\\\-2y=10+12\\\\-2y=22\ \ /:(-2)\\\\y=-11\\\\\\\begin{cases}x=-6\\y=-11\end{cases}[/tex]